1995
DOI: 10.1021/jm00006a013
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity and Selectivity on 5-HT1A Receptor of 1-Aryl-4-[(1-tetralin)alkyl]piperazines. 2

Abstract: Several 4-alkyl-1-arylpiperazines that present a tetralin moiety on the terminal part of the side chain were synthesized in order to increase the selectivity on the 5-HT1A versus D-2, alpha 1, sigma, and other 5-HT receptors. Many changes have been effected on previous structures of type 3(1-aryl-4-[3-(1,2-dihydronaphthalen-4-yl)-n-propyl]piperazines). Several synthetic procedures were followed to obtain the final products, depending on the presence or absence of a double bond, as well as of a heteroatom on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 7 publications
5
86
0
1
Order By: Relevance
“…In step b, the Grignard addition reaction afforded, in 90 % yield, the corresponding 1-cyclopropylindan-1-ol 3 which, by the action of 33 % HBr in acetic acid (step c), smoothly underwent the expected rearrangement (79 %). [36] The bromopropylidene derivative 4 was a suitable substrate to go on with the synthesis; in fact, as a 3:1 mixture of geometric isomers, it was submitted to the three steps of sequence d to yield the indanylidene compound 5 with a tethered acetamido group (63 % overall yield). In step e, trimethylsilylpolyphosphate (PPSE) promoted dehydration of the secondary amide function to generate the pivotal nitrilium ion that, by quenching onto the exocyclic olefin moiety, eventually yielded the target compound 6.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…In step b, the Grignard addition reaction afforded, in 90 % yield, the corresponding 1-cyclopropylindan-1-ol 3 which, by the action of 33 % HBr in acetic acid (step c), smoothly underwent the expected rearrangement (79 %). [36] The bromopropylidene derivative 4 was a suitable substrate to go on with the synthesis; in fact, as a 3:1 mixture of geometric isomers, it was submitted to the three steps of sequence d to yield the indanylidene compound 5 with a tethered acetamido group (63 % overall yield). In step e, trimethylsilylpolyphosphate (PPSE) promoted dehydration of the secondary amide function to generate the pivotal nitrilium ion that, by quenching onto the exocyclic olefin moiety, eventually yielded the target compound 6.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…Subsequent studies, however, indicated that this compound exerted partial agonist properties at relatively high concentrations (Lanfumey et al, 1993). , an arylpiperazine derivative, has a high affinity for the 5-HT 1A receptors (K i 5 0.6 nM), but it also has a high potency for the a-1 receptor (Greuel and Glaser, 1992;Perrone et al, 1995;Raghupathi et al, 1991). In addition, NAN-190 displays partial agonist-like activity (Fornal et al, 1994;Rydelek-Fitzgerald et al, 1990;Wozniak et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, the hypothesis that the amido function does not stabilize the 5-HT 1A receptor-ligand complex has been confirmed by us in a recent work 1 on alkylamido derivatives of 1-aryl-4-[(1-tetralinyl)alkyl]piperazines, 1, where the corresponding desamido compounds 2a-c showed the highest affinity for the 5-HT 1A receptor. 11,12 So it can be stated that the amide function is not required for binding with the 5-HT 1A receptor.…”
mentioning
confidence: 99%